Новые виды жуков-щелкунов (Coleoptera, Elateridae) из Закавказья - Долин, В.Г.; Агаев, Б.И. (Вестник зоологии, 1993)
Two click-beetle species are described as new: Zorochrus interpositus sp. n. (Z. ibericus group) from Nakhitshevan; Ampedus armeniacus sp. n. (A. praeustus group) from Kadzharan vicinity, S. Armenia. Type material is deposited in the Coleoptera collection, Schmal-hausen Institute of Zoology (Kiev).